2003
DOI: 10.1007/s00464-002-9057-6
|View full text |Cite
|
Sign up to set email alerts
|

Port-site tuberculosis after laparoscopy

Abstract: In light of the explosive increase in laparoscopic surgery, there is concern about the effectiveness of sterilizing reusable laparoscopic instruments by immersion in 2% glutaraldehyde. This article describes the clinical features of eight patients who presented with biopsy-proven tuberculosis at the port-site unassociated with other clinical features of tuberculosis. Three of the eight patients had positive cultures for Mycobacterium tuberculosis. The port-site sinuses healed with antituberculous chemotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 11 publications
2
25
1
3
Order By: Relevance
“…Usually the current practice in India is to immerse instruments in 2-2.5% glutaraldehyde solution for 20 minutes which achieves disinfection but not sterilization. 12 Furthermore, the source of infection is often the boiled tap water used for cleansing of the instruments after immersion in glutaraldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…Usually the current practice in India is to immerse instruments in 2-2.5% glutaraldehyde solution for 20 minutes which achieves disinfection but not sterilization. 12 Furthermore, the source of infection is often the boiled tap water used for cleansing of the instruments after immersion in glutaraldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the standard sterilization procedure has been a 20 minute exposure to 2.0-2.5% glutaraldehyde. At the current exposure time, these solutions act as high level disinfectants and not sterilants thus allowing bacterial endospores to survive [12]. Current guidelines on infection control recommend a minimum exposure time of 8-12 hours to achieve the desired level of sporicidal activity of these germicides and the use of higher concentrations (3.4%) of glutaraldehyde disinfectants.…”
Section: Discussionmentioning
confidence: 99%
“…Ramesh et al reported eight patients with biopsy-proven tuberculosis at the port site unassociated with other clinical features of tuberculosis following cholecystectomy. 4 Three of the eight patients had positive culture for Mycobacterium tuberculosis. Jagadish et al reported one such case.…”
Section: Discussionmentioning
confidence: 96%